(untitled) (Research, Society and Development, 2022)
Systemic lupus erythematosus (SLE), an autoimmune condition that causes kidney, skin, neurological, hematological, cardiological and pulmonary damage, presents a heterogeneous clinical pattern more frequently in females. Women of childbearing age are affected in greater proportion, causing damage from the exacerbation of the disease to organs fundamental to fetal development and maternal survival. In this sense, the present review aimed to understand the possible relationships between systemic lupus erythematosus, pregnancy and the neonatal period. The SciELO and PubMed (Medline) databases were used for research. Subsequently, the eligibility criteria were applied: randomized clinical trials; clinical trials; meta-analyses and articles published in the last 10 years with full text available in English and Portuguese. Of 113 articles searched and analyzed, 26 articles were included for this integrative literature review. In these studies, some situations such as current lupus activity or less than 6 months before conception, renal, pulmonary or cardiac involvement, pose great maternal and/or fetal risk, and are therefore considered inadvisable during pregnancy. In this sense, preconception counseling is recommended for women with SLE with a desire to conceive. Thus, pregnancy for women with lupus has become an increasingly safer process with the advent of more effective therapies for the treatment of the disease.